EFEK SAMPING KOSMETIK DAN PENANGANANYA BAGI KAUM PEREMPUAN - Lina Pangaribuan (Universitas Negeri Medan, 2017)
Cosmetics is an important requirement role in the field of beauty for the beauty of the human body that is in need in appearance. Nowadays there are many cosmetic products circulating in the market with various brands and shapes also found dangerous materials in cosmetic products sold in the market. Dangerous substances are commonly found in whitening, anti-aging, and some makeup cosmetics. Some ingredients that have been banned by the Food and Drug Administration (BPOM) on cosmetic products include mercury, hydroquinone, retinoic acid, red dye, Rhodamine B. While this hazardous material can cause irritation, allergies, physical blockage, local or systemic poisoning even affect the network system and other important organs. So the side effects of cosmetics are now becoming increasing both in quality and quantity. Therefore special handling and underlying knowledge are needed to deal with all cosmetic issues. Knowledge of cosmetics can help in determining the cosmetics to be used. Consumers should be selective in choosing cosmetics products in order to avoid mistakes in choosing cosmetics so that the negative impact of cosmetic use can be avoided. Side effects of using this illegal cosmetic can be very harmful to the human body. Side effects resulting from this cosmetic can continuously result in the outbreak of cancer, heart failure. The chemicals contained in the cosmetics can exceed the standards used for cosmetics that can raise health risks. Unconsciously the condition is caused by carelessness of the consumer as a user, while doing unconscious daily activities, so that the chemical substances into the body.